Measuring self-reported health in low-income countries: piloting three instruments in semi-rural Burkina Faso - Yulia Blomstedt; Aurélia Souares; Louis Niamba; Ali Sie; Lars Weinehall; Rainer Sauerborn (Taylor & Francis Group, 2012)
Background: National surveys in low-income countries increasingly rely on self-reported measures of health. The ease, speed, and economy of collecting self-reports of health make such collection attractive for rapid appraisals. However, the interpretation of these measures is complicated since different cultures understand and respond to the same question in different ways. Objective: The aim of this pilot study was to develop a culturally sensitive tool to study the self-reported health (SRH) of the local adult population in Burkina Faso. Design: The study was carried out in the 2009 rainy season. The sample included 27 men and 25 women aged 18 or older who live in semi-urban Nouna, Burkina Faso. Three culturally adapted instruments were tested: a SRH question, a wooden visual analogue scale (VAS), and a drawn VAS. Respondents were asked to explain their answers to each instrument. The narratives were analyzed with the content analysis technique, and the prevalence of poor SRH was estimated from the quantitative data by stratification for respondent background variables (sex, age, literacy, education, marital status, ethnicity, chronic diseases). The correlation between the instruments was tested with Spearman's correlation test. Results: The SRH question showed a 38.5% prevalence of poor SRH and 44.2% prevalence with both VAS. The correlation between the VAS was 0.89, whereas the correlation between the VAS and the SRH question was 0.60–0.64. Nevertheless, the question used as the basis of each instrument was culturally sensitive and clear to all respondents. Analysis of the narratives shows that respondents clearly differentiated between the various health statuses. Conclusion: In this pilot, we developed and tested a new version of the SRH question that may be more culturally sensitive than its non-adapted equivalents. Additional insight into this population's understanding and reporting of health was also obtained. A larger sample is needed to further study the validity and reliability of the SRH question and the VAS and understand which instrument is best suited to study SRH in the low-income setting of semi-rural Burkina Faso.